2005
DOI: 10.1002/cne.20506
|View full text |Cite
|
Sign up to set email alerts
|

C‐fiber (Remak) bundles contain both isolectin B4‐binding and calcitonin gene‐related peptide‐positive axons

Abstract: Unmyelinated nerve fibers (Remak bundles) in the rodent sciatic nerve typically contain multiple axons. This study asked whether C-fiber bundles contain axons arising from more than one type of neuron. Most small neurons of the lumbar dorsal root ganglion (DRG) are either glial cell line-derived neurotrophic factor dependent or nerve growth factor dependent, binding either isolectin B4 (IB4) or antibodies to calcitonin gene-related peptide (CGRP), respectively. Injection of IB4-conjugated horseradish peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…It may reflect two separate things; one is that, as in the mouse, CGRP-and IB4-positive DRG neurons are separate populations (Molliver et al, 1997;Zwick et al, 2002), yet certain parts of their terminal fields in the dorsal horn are tightly intertwined (see Luo et al, 2007 for more details). The other is that some CGRPpositive neurons also bind IB4, which would be consistent with findings in the DRG (Petruska et al, 2000(Petruska et al, , 2002Murinson et al, 2005;Price and Flores, 2006). The overlap in terminal fields may reflect the subpopulation of doublelabeled afferents as suggested by the observation of thin optical sections at high magnifications (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It may reflect two separate things; one is that, as in the mouse, CGRP-and IB4-positive DRG neurons are separate populations (Molliver et al, 1997;Zwick et al, 2002), yet certain parts of their terminal fields in the dorsal horn are tightly intertwined (see Luo et al, 2007 for more details). The other is that some CGRPpositive neurons also bind IB4, which would be consistent with findings in the DRG (Petruska et al, 2000(Petruska et al, , 2002Murinson et al, 2005;Price and Flores, 2006). The overlap in terminal fields may reflect the subpopulation of doublelabeled afferents as suggested by the observation of thin optical sections at high magnifications (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting to note that Remak bundles in the normal nerve milieu have been profiled as containing CGRP and IB4 representatives (Murinson et al, 2005). This fact is consistent with the physical character of these neurons, which generally range in size from medium to small and thus comprise a large proportion of the unmyelinated population.…”
Section: Cnc-induced Alteration In Neuronal Gene Expressionsupporting
confidence: 68%
“…More neurons expressing both markers are found in dorsal root ganglia compared to the trigeminal ganglion of rat [33]. Electron microscopy showed that IB4 and CGRP expressing axons were distinct, but both could be present in the same bundle of un-myelinated fibers [34]. …”
Section: Discussionmentioning
confidence: 99%